A propagation tool to connect remote-sensing observations with in-situ measurements of heliospheric structures. (1st November 2017) - Rouillard, A.P.; Lavraud, B.; Génot, V.; Bouchemit, M.; Dufourg, N.; Plotnikov, I.; Pinto, R.F.; Sanchez-Diaz, E.; Lavarra, M.; Penou, M.; Jacquey, C.; André, N.; et al.
Abstract: The remoteness of the Sun and the harsh conditions prevailing in the solar corona have so far limited the observational data used in the study of solar physics to remote-sensing observations taken either from the ground or from space. In contrast, the 'solar wind laboratory' is directly measured in situ by a fleet of spacecraft measuring the properties of the plasma and magnetic fields at specific points in space. Since 2007, the solar-terrestrial relations observatory (STEREO) has been providing images of the solar wind that flows between the solar corona and spacecraft making in-situ measurements. This has allowed scientists to directly connect processes imaged near the Sun with the subsequent effects measured in the solar wind. This new capability prompted the development of a series of tools and techniques to track heliospheric structures through space. This article presents one of these tools, a web-based interface called the 'Propagation Tool' that offers an integrated research environment to study the evolution of coronal and solar wind structures, such as Coronal Mass Ejections (CMEs), Corotating Interaction Regions (CIRs) and Solar Energetic Particles (SEPs). These structures can be propagated from the Sun outwards to or alternatively inwards from planets and spacecraft situated in the inner and outer heliosphere. In this paper, we present the global architecture of the tool, discuss some of the assumptions made to simulate the evolution of the structures and show how the tool connects to different databases.